2012
DOI: 10.1016/j.febslet.2012.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Protein disulfide isomerases in neurodegeneration: From disease mechanisms to biomedical applications

Abstract: a b s t r a c tProtein disulfide isomerases (PDIs) are a family of foldases and chaperones primarily located at the endoplasmic reticulum that catalyze the formation and isomerization of disulfide bonds thereby facilitating protein folding. PDIs also perform important physiological functions in protein quality control, cell death, and cell signaling. Protein misfolding is involved in the etiology of the most common neurodegenerative diseases, including Alzheimer, Parkinson, amyotrophic lateral sclerosis, Prion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 122 publications
(185 reference statements)
2
75
0
Order By: Relevance
“…PDI is an oxidoreductase that is involved in oxidative protein folding in the endoplasmic reticulum with an emerging role in aggregation neurodegenerative diseases (5).…”
Section: Studies In Humansmentioning
confidence: 99%
“…PDI is an oxidoreductase that is involved in oxidative protein folding in the endoplasmic reticulum with an emerging role in aggregation neurodegenerative diseases (5).…”
Section: Studies In Humansmentioning
confidence: 99%
“…It is a major ER protein that functions as a molecular chaperone and a folding enzyme by catalyzing the formation, cleavage, and rearrangement of the disulfide bonds in unfolded or misfolded proteins [3][4][5] . Recent studies have convincingly demonstrated that PDI indeed plays important roles in both the physiology and pathophysiology of disease states including diabetes [29] , cardiovascular diseases [30] , cancer [32] , neurodegenerative conditions [33] and the entry of pathogens in infectious diseases [34] . However, the precise roles for PDI in these diseases states have not yet been established.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have convincingly shown that PDI plays important roles in the physiology as well as pathophysiology of the disease states including diabetes [28] , cardiovascular diseases [66] , cancer [67] neurodegenerative conditions [68] and the entry of pathogens in infectious diseases [69] . However, the precise roles for PDI in each of these diseases have not yet been elucidated.…”
Section: Role Of Pdi In Diseases Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…PDI has been shown to accumulate with neurofibrillary tangles and the dystrophic neurites of senile plaques in AD brain, and with FUS-positive ubiquitinated inclusions in human ALS patient spinal cords (107,108). Not only was there an increase in PDI expression in AD, PD, and ALS brain, the amount of S-nitrosylated PDI was also substantial (107,(109)(110)(111)(112)(113)(114)(115). S-nitrosylation of PDI, through the redox-active thiols of the a and a' domains, inhibits enzyme activity.…”
Section: The Role Of Hbcat In Protein Folding and Redox-chaperone Actmentioning
confidence: 99%